2023
DOI: 10.1039/d3na00097d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of MgO's base characteristics by blending it with amphoteric ZnO facilitating the selective glucose isomerization to fructose for bioenergy development

Abstract: Fructose serves as an important intermediate in the preparation of liquid fuel compounds. Herein, we report its selective production via a chemical catalysis method over ZnO/MgO nanocomposite. The blending of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has been noted that in the composites, the diffraction peaks of zirconia corresponding to (101) and (112) crystal faces undergo a discernible shift towards higher 2θ angles. Additionally, these diffraction peaks appear broader, suggesting the incorporation of magnesium atoms into the zirconia lattice [25,29,30].…”
Section: Characterization Of the Synthesized Mgo/zro 2 Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that in the composites, the diffraction peaks of zirconia corresponding to (101) and (112) crystal faces undergo a discernible shift towards higher 2θ angles. Additionally, these diffraction peaks appear broader, suggesting the incorporation of magnesium atoms into the zirconia lattice [25,29,30].…”
Section: Characterization Of the Synthesized Mgo/zro 2 Catalystsmentioning
confidence: 99%
“…For instance, Rabee et al prepared magnesium-zirconium composite metal oxides with different ratios by calcining magnesium-zirconium hydrotalcite, which offered a fructose yield close to 30% with a selectivity of 74% at 95 • C for 3 h [24]. Similarly, Mahala et al found that amphoteric zinc oxide is able to modulate the acidity and base of the magnesium-zinc composite oxides, giving a fructose yield of 30 wt% with a selectivity of nearly 80 wt% [25]. Although these magnesium-based metal oxides have achieved better catalytic activity, they are more cumbersome and time-consuming to prepare.…”
Section: Introductionmentioning
confidence: 99%